COMMUNICATION STRATEGY OF CBP RUPIAH EDUCATORS TOWARDS THE SOCIALIZATION OF THE CINTA BANGGA PAHAM RUPIAH PROGRAM IN NORTH SUMATRA - Ardy Akbar Pratama; Abdul Rasyid (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Cinta Bangga Paham (CBP) Rupiah Program is a Bank Indonesia initiative to strengthen public understanding of the rupiah as a symbol of national sovereignty and a legitimate means of payment. This study aims to analyze educators' communication strategies, media use, and challenges in disseminating the program at the Bank Indonesia Representative Office of North Sumatra Province. A descriptive qualitative approach was employed using in-depth interviews, observation, and documentation. Informants included the CBP Rupiah Coordinator, internal Bank Indonesia educators, and external educators from the CBP Rupiah Youth Ambassadors. Data were analyzed through data reduction, data display, and conclusion drawing. Educators adapted messages to audience characteristics, used simple and contextual language, applied interactive methods, and utilized presentations, educational videos, social media, posters, and instructional materials. Strategy selection was influenced by audience characteristics, educational objectives, geographical conditions, and media developments. Challenges included differences in public understanding, limited time, wide dissemination areas, and unequal technology access. Conclusion: Adaptive, interactive, and audience-oriented communication strategies support effective CBP Rupiah dissemination in North Sumatra.